First insights on Black Soldier Fly (Hermetia illucens L.) larvae meal dietary administration in Siberian sturgeon (Acipenser baerii Brandt) juveniles - Caimi C.; Renna M.; Lussiana C.; Bonaldo A.; Gariglio M.; Meneguz M.; Dabbou S.; Schiavone A.; Gai F.; Elia A. C.; Prearo M.; Gasco L. (Aquaculture, 2020)
The Hermetia illucens (L.) larvae meal (HIM) has been tested on different fish species but its use on Siberian sturgeon has not been investigated yet. The aim of this study was to evaluate the effects of fish meal (FM) substitution with a highly defatted HIM on growth performance, biometric and morphometric indices, apparent digestibility of diets, whole body proximate and fatty acid compositions of Acipenser baerii (Brandt) juveniles. Five experimental groups were fed with a FM-based diet without HIM (HIM0), three diets with 25% (HIM25), 50% (HIM50) and 100% (HIM100) of FM substitution with HIM, or a vegetable protein based diet (VEG) without HIM. The feeding trial lasted 118 days and 4 replicates per diet were used. The HIM100 diet was refused by the fish and therefore this experimental group was excluded from statistical evaluation. Moreover, a decrease in feed consumption was recorded with the increase of HIM inclusion. The HIM50 diet negatively affected the growth performance of the fish. The somatic indices were not affected by treatment. Increasing levels of HIM showed increases of dry matter and ether extract contents in the whole body. Compared to HIM0, HIM diets caused modification in lauric acid (up to 65-fold increase) and total saturated fatty acids (up to 1.4-fold increase) contents in the fish whole body. The apparent digestibility coefficients of dry matter, crude protein and gross energy were the highest for the VEG diet (77.0%, 90.4% and 85.8%, respectively). HIM25 and HIM50 showed lower apparent digestibility coefficients of crude protein (86.5% and 86.6%, respectively) when compared to HIM0 (88.5%). Overall, this study showed that it is possible to replace up to 25% of FM with HIM in the diet of Siberian sturgeons (equal to 18.5% HIM inclusion level) without affecting the growth performance, condition factor, biometric and morphometric indices, and whole body proximate composition of the fish. The fatty acid composition of the sturgeons’ whole body was significantly modified already at 18.5% ...